Quality of Academic Advising and Student Support Services from the Perspective of Preparatory Year Students at the University of Najran - Muhammad Abdo Muhammad Salim; Muhammad Omar Al-Sayed Amin; Mona Abbas Salman Abu Marra (University of Science and Technology, Yemen, 2021)
This research aimed to measure the level of quality of academic advising and student support services from the perspective of students of Preparatory Year at the University of Najran. To achieve this, the descriptive analytical method was followed by administering a questionnaire consisting of (37 items) which were distributed over four dimensions (the academic advisor - the quality of the academic support for outstanding and struggling students - the quality of supporting talented and creative students - the quality of complaints and suggestions services). The sample consisted of (300) students selected from among the preparatory year at the University of Najran. The results indicated that the level of quality of academic advising services and student support services was (medium level) with a mean of (2.24). There were statistically significant differences at (α = 0.05) in the level of quality of academic services and student support services according to the level (first-second) in favor of the second level. There were also differences in the level of academic advising and student support services according to student status at (α = 0.05) in favor of struggling students. Results also indicated that there were no statistically significant differences in the students' assessment of the quality of services due to the gender variable. The study concluded that academic advising services need more efforts to improve the quality of services, especially in providing the necessary support to students, as well as the services for gifted and creative students, complaints and suggestions services. The study recommended the need to adopt clear mechanisms for academic advising and student support through which these services can be provided to all student categories and to evaluate the quality of these services. Keywords: academic advising, preparatory year, quality, Najran University.